(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article presents a comprehensive methodology for enhancing the professional-oriented communicative competence of cadets. Through an integration of theoretical insights and practical strategies, this approach aims to equip cadets with the necessary skills to effectively communicate in professional settings.